Disparities in Epidemiological Profile of Gastric Adenocarcinoma in Selected Cities of Brazil - Curado, Maria Paula (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Despite decreasing global incidence trends, gastric cancer is still among the five most incident cancers in the world and the third cancer-related cause of death. In Brazil, differences in incidence and mortality exist depending on the geographic region studied. OBJECTIVE: To describe the incidence, mortality, trends and age-period-cohort of gastric cancer in three cities of Brazil (Sao Paulo, Belem and Fortaleza), in the period 1990-2012. Mortality for gastric cancer in Brazil overall and by region was described. METHODS: 33,462 incident cases of gastric cancer were identified from the population-based cancer registries and 23,424 deaths from mortality information system in residents of the three cities and in Brazil were included in the study. Data for incident cases were extracted from the Population Based Cancer Registries from the National Cancer Institute (INCA). Mortality data on gastric cancer were extracted from Information Technology Department of Brazilian Public Health Care System/Health Ministry (DATASUS/MS). Mortality and incidence age standardized rates were calculated. For trends analysis the Joinpoint Regression and age-period-cohort model were applied. RESULTS: Belem presented the highest incidence rates for gastric adenocarcinoma. Decreasing incidence trends were identified in Sao Paulo (-7.8% in men; -6.3% in women) and in Fortaleza (-1.2% in men). Increasing incidence trends were observed for women in Belem (1.8%) and Fortaleza (1.1%). In Belem (Amazon area), there was an increased risk for gastric cancer in women born after the 1960s. Overall in Brazil mortality for gastric cancer is decreasing. Mortality trends showed significant reduction, for both sexes, in the three Brazilian cities. CONCLUSION: Incidence of gastric cancer is increasing in women born in the sixties in Belem (Amazon region) and Fortaleza (Northeast region). In Brazil there was increase in mortality in Northeast region and decrease in others regions. More update data on incidence for Amazon and Northeast region is needed.